The Role of Re-Entrant Microstructures in Modulating Droplet Evaporation Modes - Hoang Huy Vu; Nam-Trung Nguyen; Navid Kashaninejad (Micromachines)
The evaporation dynamics of sessile droplets on re-entrant microstructures are critical for applications in microfluidics, thermal management, and self-cleaning surfaces. Re-entrant structures, such as mushroom-like shapes with overhanging features, trap air beneath droplets to enhance non-wettability. The present study examines the evaporation of a water droplet on silicon carbide (SiC) and silicon dioxide (SiO2) re-entrant structures, focusing on the effects of material composition and solid area fraction on volume reduction, contact angle, and evaporation modes. Using surface free energy (SFE) as an indicator of wettability, we find that the low SFE of SiC promotes quick depinning and contact line retraction, resulting in shorter CCL phases across different structures. For instance, the CCL phase accounts for 55–59% of the evaporation time on SiC surfaces, while on SiO2 it extends to 51–68%, reflecting a 7–23% increase in duration due to stronger pinning effects. Additionally, narrower pillar gaps, which increase the solid area fraction, further stabilize droplets by extending both CCL and constant contact angle (CCA) phases, while wider gaps enable faster depinning and evaporation. These findings illustrate how hydrophobicity (via SFE) and structural geometry (via solid area fraction) influence microscale interactions, offering insights for designing surfaces with optimized liquid management properties.